2008
DOI: 10.1007/s12206-007-1029-2
|View full text |Cite
|
Sign up to set email alerts
|

Micromachined Si cantilever arrays for parallel AFM operation

Abstract: Silicon cantilever arrays with a very small pitch for parallel AFM operations were studied. We fabricated 1x104 in eight groups and 1x30 Si probe arrays and produced a smaller pitch (15 m) between probe tips by using Si anisotropic etching with a vertical wall shaped oxide mask. The vertical controls of Si probes were able to operate individually or in a group by integrating electrostatic actuators into the cantilevers of the probes. The fabricated Si cantilever arrays showed reasonable dynamic characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…One is to change the AFM measurement procedure from serial to parallel type [6]. This idea is usually realised by applying cantilever arrays, which are usually fabricated with integrated sensors and/or actuators using MEMS technology [7][8]. The shortcoming of this approach lies in the complicated fabrication of the sensors and the difficulties in its operation.…”
Section: Introductionmentioning
confidence: 99%
“…One is to change the AFM measurement procedure from serial to parallel type [6]. This idea is usually realised by applying cantilever arrays, which are usually fabricated with integrated sensors and/or actuators using MEMS technology [7][8]. The shortcoming of this approach lies in the complicated fabrication of the sensors and the difficulties in its operation.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have recently been enhancing the speed of AFM for the imaging of dynamic processes, mostly in the field of biophysics, with impressive results. [13][14][15][16] In these cases, the sample size is usually very small, e.g., a few mm, and the sample has small height corrugations. This makes "sample scanning" design a suitable architecture, in which the AFM cantilever is kept stationary and the sample is scanned along three axes.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have suggested parallelization of AFM as a direct approach to increasing AFM throughput in direct proportion to the number of AFM tips in an array. 12,[14][15][16][17][18] Following this path, efforts to increase the throughput of AFM using arrays of cantilevers have been made, instead of a single cantilever, motivated by advances in microsystems fabrication 3 technologies and CMOS processes. Examples include data storage, 18 parallel imaging and force spectroscopy 12 and parallel AFM nanolithography.…”
Section: Introductionmentioning
confidence: 99%
“…Tip arrays have been pursued to increase the SPM throughput [3,4], but laborious engineering and control of individual tips are required to maintain the nanometer distance between each tip and surface. Also, precise shaping of the tip geometry by etching [5,6] or functionalization with carbon nanotubes [7] enables SPM to image nanostructures with a higher aspect ratio, but the technique still cannot image 3D overhanging structures and cavities, as well as soft samples like biological materials. This limited imaging capability was well addressed by photonic force microscopy (PFM) [8,9] that replaces the conventional stiff probe with an optically trapped, sub-micron-sized particle as a soft probe.…”
Section: Introductionmentioning
confidence: 99%